The Paris Agreement : Climate Change, Solidarity, and Human Rights - Blau, Judith (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book discusses the immediate and severe threat posed by global climate change and the various obstacles that stand in the way of action. Judith Blau presents scientific evidence relevant to The Paris Agreement (COP-21): an international treaty that promises to strengthen the global response to climate change. As she reckons with the dangers of catastrophic planetary heating, Blau discusses the clash between the deeply ingrained American tradition of individualism and the collective action and acknowledgement of intertwined fate needed to address climate change. She acknowledges that America's capitalist bent stands in contrast to the idea of the "commons"-a concept that we need to embrace if climate change is to be mitigated. The volume also explains the foundations of international human rights standards as they relate to climate change. Drawing from guiding principles of human rights and equality, the book concludes hopefully-suggesting that the people of the world can meet the challenge posed by climate change by at once acknowledging shared humanity and celebrating difference. .
Keywords: Social sciences.; Political sociology.; Environmental policy.; Welfare state.; Social justice.; Human rights.; elektronické knihy; electronic books